A New Metaphor for Language - Tarpent, Marie-Lucie (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1989)
Metaphor has often played a role in intellectual enquiry by epitomizing a general attitude of mind and providing a focal point for intellectual creativity. The metaphor of language as a biological organism, which informed and inspired nineteenth-century linguistics, has long fallen into disuse, but no new metaphor has taken its place. Saussure’s comparison of language with the game of chess failed to capture the imagination of other linguists. Today we are told that language is like nothing else, thus closing the door to even the possibility of a useful metaphor. Here, language is compared to the city, a cultural organism. By drawing parallels with another facet of culture, this new metaphor highlights many aspects of the nature, function and evolution of language. It also provides a new and different perspective on linguistics, suggesting an approach more attuned to the social and communicative functions of language.